Enhanced Photocatalytic Activity of S-Doped TiO2 Prepared via a Modified Sol-Gel Process - Hu, S.Z.; Li, F.Y.; Fan, Z.P. (Asian Journal of Chemistry, 2012)
S-Doped TiO2 was prepared via modified sol-gel process. Transmission electron microscopy (TEM), N2 adsorption, X-ray diffraction (XRD), UV-VIS spectroscopy and X-ray photoelectron spectroscopy (XPS) were conducted to characterize the prepared TiO2 particles. It is shown that the prepared TiO2 particles were around 10 nm with narrow particle size distribution. The addition of MCM-41 restricted the agglomeration and growth of TiO2 particles, thus leading to the small particle size. The photocatalytic performance in the degradation of methylene blue indicated that S-doped TiO2 showed much higher photocatalytic activity than pure TiO2 under visible light. The sulfuration time and sulfuration temperature exhibited significant influence on the photocatalytic activity of prepared TiO2 catalysts.